Trends and determinants of antenatal, intranatal, and postnatal care utilization among Indonesian women (2012–2017): associated factors in midwifery service utilization between midwives and other health professionals - Qorinah Estiningtyas Sakilah Adnani; Rufidah Maulina; Kadar Ramadhan; Niken Bayu Argaheni; Holly Powell Kennedy; Michelle Telfer (BMC Nursing)
Abstract Background Maternal healthcare services during pregnancy and childbirth are essential to reducing adverse maternal and child health outcomes, including maternal and child mortality. Midwives in Indonesia play an important role in providing maternal healthcare services. Purpose The purpose of this study is to analyze trends in midwifery care utilization for antenatal care (ANC), intranatal care (INC), and postnatal care (PNC) among Indonesian women between in 2012 and 2017, and to examine the sociodemographic, economic, and regional factors associated with access and utilization to inform strategies for improving maternal and neonatal health outcomes. Method This study uses data from the Indonesia Demographic and Health Survey (IDHS) from 2012 to 2017. A total of 15,269 women aged 15–49 from the Indonesia Demographic and Health Survey (IDHS) participated in this study, consisting of 7,712 women from the 2012 survey and 7,557 from the 2017 survey. Only respondents who completed the Women’s Questionnaire were included in the analysis. A multiple logistic regression model was used to analyze factors associated with midwives’ engagement in maternal healthcare service provision. This study used multivariate analyses for 2012 and 2017 to examine the relationships between various socio-demographic characteristics and the utilization of specific maternal health services in Indonesia. Result Several factors consistently influenced service utilization of midwifery services, including younger maternal age, secondary education, being married, without health insurance, rural residence, and higher ANC visit frequency. Women with normal births and without complications were significantly utilizing the service from midwives. Conversely, disparities remained for women in the eastern part of Indonesia and among those with higher parity. Conclusion Midwives play a critical role as accessible and trusted providers and remain central to strengthening service delivery and extending community-level reach across Indonesia. These insights offer valuable guidance for policymakers and health planners in enhancing midwife-led service coverage and improving maternal health outcomes. Clinical trial number Not applicable.